Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Pengunjung di Objek Wisata Waterpark Baradatu - Bakri, Edwin; Warga Negara, Tri Lestira Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Baradatu Waterpark Tourism Object 2017 to 2021 visitor data fluctuates. Therefore, the purpose of this research is to find a suitable marketing strategy for Baradatu Waterpark. This study uses the SWOT analysis method. Systematically examine the strengths and weaknesses of the company's internal factors, as well as opportunities and threats from the company's environment. Based on the Cartesian SWOT diagram analysis, the strategy that must be applied in this situation is to support an aggressive growth policy (growth oriented strategy) related to the industry where there are leaders called market challengers and the order is as follows. To support a growth-oriented strategy, Baradatu Waterpark is supported by an SO strategy. The SO strategy can be implemented like this: (2) Reduce ticket prices and offer discounts to visitors to please them. (3) Providing innovation in both games and water parks. Many children like water park games. Keywords: marketing strategy and increasing visitors.